E-modul Sejarah sebagai inovasi bahan ajar digital berbasis aplikasi Canva untuk meningkatkan minat belajar siswa - Adinda Fuadila Almahera; Najib Jauhari; Ulfatun Nafi’ah (Universitas Negeri Malang, 2023)
History learning is generally considered an uninteresting subject. This is because students are less interested in learning history. The use of textbooks makes it easy for students to feel bored, coupled with students' lack of interest in reading. This is what makes students' interest in learning history at MAN 2 Gresik decline. Based on these problems, the researchers developed supporting teaching materials in the form of an E-Module History based on the Canva application, material for the process of entering Islam in Gresik Regency for class X IIS 1 MAN 2 Gresik students. This teaching material is a teaching material with a format in the form of a link that can be accessed by students via smartphones by utilizing the internet network. The E-Modul History teaching materials were developed using the ADDIE development method which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The development of the History E-Module teaching materials has met the criteria with the validity values of the materials and teaching materials, namely 81.6 percent and 88.3 percent. With a test value of the effectiveness of small and large groups of 85.4 percent and 87.6 percent, respectively. History E-Module teaching materials are also made with the aim of attracting students' interest in learning history. The results of the percentage of students' interest in learning before and after are 49.8 percent and 89.8 percent which indicate an increase in student interest in learning after using the History E-Module teaching materials. Pembelajaran sejarah secara umum dipandang sebagai mata pelajaran yang tidak menarik. Hal tersebut dikarenakan kurang tertariknya siswa terhadap pembelajaran sejarah. Penggunan bahan ajar Buku Paket membuat siswa gampang merasa bosan ditambah dengan minat membaca siswa yang kurang. Hal ini yang menjadikan minat belajar siswa terhadap pembelajaran sejarah di MAN 2 Gresik menurun. Berdasarkan permasalahan tersebut peneliti memutuskan membuat bahan ajar pendukung berupa E-Modul Sejarah berbasis aplikasi canva materi proses masuknya Islam di Kabupaten Gresik untuk siswa kelas X IIS 1 MAN 2 Gresik. Bahan ajar ini merupakan bahan ajar dengan format berupa link yang bisa diakses oleh siswa melalui smartphone dengan memanfaatkan jaringan internet. Bahan ajar E-Modul Sejarah dikembangkan dengan metode pengembangan ADDIE (Analysis, Design, Development, Implementation, dan Evaluation) Pengembangan bahan ajar E-Modul Sejarah telah memenuhi kriteria dengan nilai validitas materi dan bahan ajar yakni 81,6 persen dan 88,3 persen. Dengan nilai uji efektivitas kelompok kecil dan besar sebesar 85,4 persen dan 87,6 persen. Bahan ajar E-Modul Sejarah juga dibuat dengan tujuan untuk menarik minat belajar siswa dalam belajar sejarah. Hasil persentase minat belajar siswa sebelum dan sesudah yakni 49,8 persen dan 89,8 persen yang menunjukkan adanya kenaikan minat belajar siswa setelah menggunakan bahan ajar E-Modul Sejarah.